Fostering Gender-Transformative Change in Sustainable Forest Management : The Case of the Dedicated Grant Mechanism (DGM) - Canpolat, Ezgi (Washington, DC: World Bank, 2022)
Since 2015, the Dedicated Grant Mechanism for Indigenous Peoples and Local Communities (DGM) has provided a unique model for inclusive and bottom-up approaches to delivering climate finance for sustainable forest management. Through 12 country-level programs designed and implemented by Indigenous Peoples and Local Communities (IPLCs), the DGM is guiding investment of around $80 million and impacting the livelihoods of over 200,000 people. DGM supported activities are intended to be designed and implemented in a gender-responsive and socially inclusive manner and aim to improve key gender equality outcomes based on the particular and varied contexts of DGM countries.